PENCEGAHAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE DENGAN LARVASIDA DI MAN 1 SAMPANG - Ahmadi, Ahmadi; Widyyati , Mei Lestari Ika; Mery Eka Yaya Fujianti; Atika Jatimi (Gayaku Publisher, 2024)
Dengue hemorrhagic fever (DHF) is a significant public health issue in Indonesia, including in Sampang Regency. This community service program aimed to enhance the understanding and awareness of students, teachers, and staff at MAN 1 Sampang regarding DHF prevention through education and the implementation of the 3M Plus method. The program methods included preparing educational materials, conducting interactive seminars, small group discussions, demonstrations, hands-on practices, and evaluations using pre-test and post-test questionnaires. The results showed a significant increase in participants' knowledge, from 40% before the activity to 85% afterward. Participants also reported greater confidence in identifying and eliminating mosquito breeding sites. Post-activity monitoring revealed that 80% of the school environment was free from potential mosquito habitats, although some areas still required special attention. The main challenge identified was raising community awareness to maintain environmental cleanliness.In conclusion, this program effectively increased awareness of DHF prevention in the school environment. It is recommended to establish a student health team, conduct periodic programs, and collaborate with local health centers to ensure program sustainability. The implementation of these measures is expected to serve as a model for other schools in preventing DHF cases.